PELATIHAN PENANGANAN DASAR HEWAN COBA BAGI LABORAN BERBAGAI PERGURUAN TINGGI FARMASI DI PROVINSI NTB - Raisya Hasina; Siti Rahmatul Aini; Iman Surya Pratama; Mahacita Andanalusia; Yoga Dwi Saputra; Baiq Dwiyan Nugrahani; Yazid Maula Arzaqi (Jurnal Abdi Insani, 2023)
The use of experimental animals in drug research needs to be done before testing on humans. The increase in the use of experimental animals and ethical demands in pharmaceutical research have encouraged an increase in the capacity of laboratory staff in a sustainable manner, including in the Province of West Nusa Tenggara (NTB). Animal welfare greatly influences research results. The concept of welfare in question is "Five Freedom". In addition, the principles of replacement, reduction, refinement must also be fulfilled. This needs to be considered in order to get valid research results. The purpose of this activity is to train and support the basic knowledge and skills of laboratory assistants in handling experimental animals at Pharmacy colleges in West Nusa Tenggara. The training was conducted at the pharmacology laboratory of the Pharmacy Study Program, Faculty of Medicine, University of Mataram. The training begins with giving the participants a pretest, followed by delivery of materials and workshops to increase knowledge regarding the process of handling experimental animals, then ends with the participants filling out the posttest. After delivering the material and workshops, an increase in evaluation results was obtained in the form of an increase in the posttest scores of the participants related to knowledge about the material handling of the experimental animals presented. The average pretest score was 63.00 Â± 21.11 with a score of 20.00 (lowest) and 90.00 (highest), experiencing an increase in knowledge based on the posttest average score of 74.00 Â± 14.97 with a score of 60.00 (lowest) and 100.00 (highest). Conclusion: This training activity can increase the knowledge and skills of laboratory assistants at various pharmaceutical colleges in NTB regarding the basic handling of experimental animals.